A novel method of evaluating semantic intrusion errors to distinguish between amyloid positive and negative groups on the Alzheimer's disease continuum. (May 2020) - Curiel Cid, Rosie E.; Crocco, Elizabeth A.; Duara, Ranjan; Garcia, Jessica M.; Rosselli, Monica; DeKosky, Steven T.; Smith, Glenn; Bauer, Russell; Chirinos, Cesar L.; Adjouadi, Malek; Barker, Warren; Loewenstein, David A.
Abstract: Background: The development and validation of clinical outcome measures to detect early cognitive decline associated with Alzheimer's disease (AD) biomarkers is imperative. Semantic intrusions on the Loewenstein Acevedo Scales of Semantic Interference and Learning (LASSI-L) has outperformed widely used cognitive measures as an early correlate of elevated brain amyloid in prodromal AD and has distinguished those with amnestic mild cognitive impairment (aMCI) and high amyloid load from aMCI attributable to other non-AD conditions. Methods: Since intrusion errors on memory tasks vary widely, we employed a novel method that accounts for the percentage of intrusion errors (PIE) in relation to total responses. Individuals with either high or low amyloid load across the spectrum of aMCI and dementia and amyloid negative cognitively normal older adults (CN) were studied. Results: Mean PIE on indices sensitive to proactive semantic interference (PSI) and failure to recover from proactive semantic interference (frPSI) could distinguish amyloid positive from amyloid negative aMCI and dementia groups. Number of correct responses alone, while able to differentiate the different diagnostic groups, did not differentiate amyloid positive aMCI from their counterparts without amyloid pathology. Conclusions: PIE, a novel and sensitive index of early memory dysfunction, demonstrated high levels of sensitivity and specificity in differentiating CN from amyloid positive persons with preclinical AD. Mean levels of PIE are higher for amyloid positive aMCI and dementia participants relative to their amyloid negative counterparts.